Analysis of Income and Feasibility of Shallot Farming (Allium ascalonicum, L) Group of Combined farmer groups “Tani Hasil” from Gandasuli Village, Brebes Regency: Analysis of Income and Feasibility of Shallot Farming (Allium ascalonicum, L) Group of Gapoktan â€œTani Hasilâ€ from Gandasuli Village, Brebes Regency - Muhammad Juwanda; Suci Nur Utami; Muhammad Dini Adita; Khusnul Khotimah; Yan El Rizal Unzilatirrizqi (Jurnal Online Pertanian Tropik, 2024)
Shallot (Allium ascalonicum, L) is one of the leading agricultural commodities in Brebes Regency which is the national shallot center. Analysis of income and feasibility of shallot farming in Brebes has never been studied. This research was conducted to determine the study of income analysis and the feasibility of shallot farming carried out by farmers who are members of a combined farmer group (Gapoktan) Gandasuli sub-district, Brebes Regency. This research was conducted from February to March 2023 on shallot farmers at the Gapoktan located in Gandasuli Village, Brebes District, Brebes Regency. The location selection was carried out purposively with the consideration that Gapoktan is a combination of farmer groups that consistently cultivate shallots throughout the year. The research method used in this study is a qualitative method with a case study type of research. The data used are primary data and secondary data. The shallot farming business obtained a total farmer income of Rp. 200,000,000 with a total production cost of Rp. 152,110,000 and the income received is IDR 47,890,000. The results of the analysis obtained the R/C ratio value of 1.315 which indicates that the shallot farming carried out by Gapoktan "Tanihasil" Gandasuli Village, Brebes Regency is feasible to cultivate with a BEP value of Rp. 190,140,000. Farmers with a productive age and long experience working in shallot farming will influence the success of shallot cultivation.